Diagnostic Potential of Plasma Extracellular Vesicle miR-483-3p and Let-7d-3p for Sepsis - Qiu, Guanguan; Fan, Jiajie; Zheng, Guoping; He, Jiangping; Lin, Fangping; Ge, Menghua; Huang, Lanfang; Wang, Jiangmei; Xia, Jie; Huang, Ruoqiong; Shu, Qiang; Xu, Jianguo (Frontiers in Molecular Biosciences, 2022)
Background: microRNAs (miRNAs) from circulating extracellular vesicles (EVs) have been reported as disease biomarkers. This study aimed to identify the diagnostic value of plasma EV-miRNAs in sepsis. Methods: EVs were separated from the plasma of sepsis patients at admission and healthy controls. The expression of EV-miRNAs was evaluated by microarray and qRT-PCR. Results: A preliminary miRNA microarray of plasma EVs from 3 sepsis patients at admission and 3 healthy controls identified 11 miRNAs with over 2-fold upregulation in sepsis group. Based on this finding, EV samples from a cohort of 37 sepsis patients at admission and 25 healthy controls were evaluated for the expression of the 6 miRNAs relating injury and inflammation via qRT-PCR. Elevated expression of miR-483-3p and let-7d-3p was validated in sepsis patients and corroborated in a mouse model of sepsis. miR-483-3p and let-7d-3p levels positively correlated with the disease severity. Additionally, a combination of miR-483-3p and let-7d-3p had a diagnostic value for sepsis. Furthermore, bioinformatic analysis showed that miR-483-3p and let-7d-3p target pathways regulating immune response and endothelial function. Conclusion: The present study reveals the potential role of plasma EV-miRNAs in the pathogenesis of sepsis and the utility of combining miR-483-3p and let-7d-3p as biomarkers for early sepsis diagnosis.